The macrocyclic lactone oxacyclododecindione reduces fibrosis progression - Saurin, Sabrina; Meineck, Myriam; Rohr, Markus; Roth, Wilfried; Opatz, Till; Erkel, Gerhard; Pautz, Andrea; Weinmann-Menke, Julia (Frontiers in Pharmacology, 2023)
Background: Renal fibrosis is one of the most important triggers of chronic kidney disease (CKD), and only a very limited number of therapeutic options are available to stop fibrosis progression. As fibrosis is characterized by inflammation, myofibroblast activation, and extracellular matrix (ECM) deposition, a drug that can address all these processes might be an interesting therapeutic option. Methods: We tested in vivo in an ischemia–reperfusion (I/R) model in C57BL/6 mice and in kidney tubular epithelial cells (TEC) (HK2 cell line and primary cells) whether the natural product oxacyclododecindione (Oxa) reduces fibrosis progression in kidney disease. This was evaluated by Western blot, mRNA expression, and mass spectrometry secretome analyses, as well as by immunohistochemistry. Results: Indeed, Oxa blocked the expression of epithelial–mesenchymal transition marker proteins and reduced renal damage, immune cell infiltration, and collagen expression and deposition, both in vivo and in vitro. Remarkably, the beneficial effects of Oxa were also detected when the natural product was administered at a time point of established fibrotic changes, a situation close to the clinical situation. Initial in vitro experiments demonstrated that a synthetic Oxa derivative possesses similar features. Conclusion: Although open questions such as possible side effects need to be investigated, our results indicate that the combination of anti-inflammatory and anti-fibrotic effects of Oxa make the substance a promising candidate for a new therapeutic approach in fibrosis treatment, and thus in the prevention of kidney disease progression.